Analysis of the effect of particle size on permeability in hydrate-bearing porous media using pore network models combined with CT. (1st January 2016) - Wang, Jiaqi; Zhao, Jiafei; Zhang, Yi; Wang, Dayong; Li, Yanghui; Song, Yongchen
Highlights: Pore network model with CT provides a nondestructive way of obtaining the porosity. Increasing pore and throat radii increases the absolute permeability in hydrates. Larger porosity induces a larger water but a smaller gas relative permeability. Abstract: Because of the clean burning and minimal pollution generation of natural gas hydrates, they are viewed as premium fuel energy. The gas and water flow is highly dependent on the seepage properties of the hydrate sediments; therefore, the permeability is a key parameter for estimating the gas production of hydrate reservoirs. Pore network models combined with X-ray computed tomography (CT) were proposed to analyze the index properties and percolation characteristics of porous media containing hydrates in our previous study. This study extends our previous investigation into the influences of particle size and porosity on permeability. The results suggest the porosities of hydrate-bearing porous media formed by different-size particles, as calculated by both the pore network models and the volumetric method, are in agreement. Moreover, the hydrate-bearing porous media formed by larger-size particles has larger porosity, smaller capillary pressure, and larger absolute permeability. In addition, under the same degree of water saturation, larger porosity induced a larger water-phase relative permeability, but a smaller gas-phase relative permeability.